STUDI ANALISIS IKLIM PADA TAPAK KOMPLEK BALIKPAPAN SPORT dan CONVENTION CENTER - Abdul Mattin; Derie Annisa; Dian Fraisa; Fajri Nur Rachman (Display Architecture Journal, 2022)
Climate and the movement of the sun have a high influence on a building site. The Balikpapan Sport & Convention Center building is a landmark of the city of Balikpapan, This study aims to identify the condition of the movement of the sun on the site in a period of one year and how it impacts the surrounding environment. This study uses a qualitative paradigm approach with the sunearthtool software analysis tool, at the site of the Balikpapan Sport & Convention Center Building. This study concluded that the site location of the Balikpapan Sport & Convention Center Building is in the path of the sun's circulation, which peaks in the period from January to April at 250-110 degrees. In this period every day the sun shines fully in 12 hours. In the simulation, it was found that the highest time of exposure to the side of the building was at 09:00 am and 15:00 pm. The shape of the building is in the form of a circle/tube, resulting in maximum exposure to the sun evenly on both sides of the building.